Az évszak és az azonos évszakban történt ismételt mintavételek hatása holstein tenyészbikák ejakulátumának minőségi- és mennyiségi jellemzőire - Tőzsér, János; Mézes, Miklós; Várszegi, József; Szász, Ferenc (Acta Agraria Debreceniensis, 2002)
This study was carried out at the Hungarian National Artificial Insemination Centre in order to evaluate the seasonal effects on the quantitative and qualitative parameters of sperm production using sperm analyser equipment. The volume of ejaculate (VE), percentage of living sperm (PLS), spermatozoa concentration (SC), motility score (MC), percentage of motile spermatozoa (PMS), speed of movement of sperm cells (SMS) and the percentage of sperm cells moving straightforward (PSMS) were collected and observed in three seasons (summer, autumn, winter) in Holstein-Friesian breeding bulls (n = 15). The sperm collection was done for three successive weeks in every season on the same day (summer: n = 41, autumn: n=39, winter: n = 42, altogether: n = 122). The same sperm samples were measured by sperm analyser equipment (HTM version 7.0, Danvers) for PMS, SMS and PSMS. The seasonal and the number of sperm collection effects were confirmed on semen characteristics by multiple analysis of variance (two ways MANOVA, Type III) using the program package of STATISTICA 4.5. The average values of VE were similar in the three seasons (summer: from 4.42 to 6.28 cm3, autumn: from 4.08 to 6.86 cm3, winter: from 5.43 to 5.71 cm3). The average values of the MC were similar in each of the three seasons (summer: from 3.66-4.00 M; autumn: from 3.66-3.77 M; winter: from 3.86-4.07 M). The summary of all effects for season (P<0.001), repeated sperm collections in the same season (P<0.05) and interaction of two traits (P<0.01) were established on the measured characteristics. The special effects (P<0.05) of a given season were calculated, excepting the VE and MC, on all of the measured characteristics. The special effect (P<0.01) of the repeated sperm collections in the same season was verified in only one case (SMS). It is not surprised at the interaction was established on the VE (P<0.001), PMS (P<0.05), and SMS (P<10.0). The results of present study suggest that seasonal effect on sperm quality of breeding bulls cannot be eliminated even at standard feeding and keeping conditions. Considering our results, we can recommend that the average values of three successive weeks in every season be used, to take advantage of seasonal effect on the quantitative and qualitative parameters of sperm production.